RANCANG BANGUN PLATFORM PENGGALANGAN DANA MASJID BERBASIS WEBSITE DENGAN METODE CROWDFUNDING - Suci Mutiara; Muhammad Miftah Murod (Politeknik Bisnis Indonesia, 2022)
Every social service institution definitely needs funds to carry out various service programs, one of which is raising funds for the construction of mosques or mosque renovations. Thus, there are still many mosques that raise funds by taking to the streets and asking road users, so that it can hinder the smooth flow of traffic, as well as many mosque charity boxes in every shopping center and in one shopping center there can be two to three mosque charity boxes. which exists. In this study, use the website as a research base that aims to mobility towards its use. The system that will be built will use the CodeIgniter Framework as a framework in the development of the Crowdfunding system. In this study using the prototype with the consideration that the prototype is easier to implement and has a smaller risk of failure. This application is designed using Java Programming Language, HTML5 Bootstrap, codeigniter and MYSQL database. Software testing results have been tested using the Black-Box Testing method. the result is that the menu button on the website can work properly and the website can be run on all smart phones. The results of this study are in the form of a Website-Based Mosque Fundraising Platform with the Crowdfunding Method which can accommodate donors to give alms and mosque administrators can make mosque charity fundraising either for renovation or construction.